Advanced Functional Fibrous Materials for Enhanced Thermoregulating Performance - Pakdel, Esfandiar; Naebe, Maryam; Sun, Lu; Wang, Xungai (ACS applied materials & interfaces, 2019)
The concept of thermoregulating textiles capable of providing personal thermal management property (PTM) has attracted significant attention in recent years. It is considered as an emerging approach to promote the comfort and general well-being of wearers and also to mitigate the energy consumption load for indoor living space conditioning. Regulating the heat exchange between human body and environment has been the core subject of many studies on introducing the PTM functionality to textiles. This work provides an overview of the latest literature, summarizing the recent innovations and state-of-the-art approaches of controlling the heat gain and loss of textiles. To this end, methods to control the fundamental aspects of heat gain and loss of fabrics such as using near-infrared reflective materials and conductive nanomaterials, designing photonic structures of fabrics, and engineering nanoporous structures for passive cooling and heating effects will be discussed. Moreover, specific attention is given to the application of phase change materials in textiles, their integration methods, and the associated mechanisms. Several commercial methods such as adapting the innovative designs, introducing moisture management capability, and using air/liquid thermoregulating systems will also be discussed. This review article provides a clear picture of the concept of thermoregulating textiles and recommends some future research trajectories for this emerging field.